Factors influencing tourist satisfaction while traveling among students At universiti malaysia kelantan - Muhammd Hisam Mohd Nawawi; Muhammad Aizat Mohamad Sayoti; Muhammad Amir Izzat Mohd Sharif; Muhammad Ammar Mohd Arifin (2022)
This study's main goal is to investigate factors that influence tourists' satisfaction while travelling among students at University Malaysia Kelantan. This study is required to give us a better understanding of the various aspects of student travellers from University Malaysia Kelantan's satisfaction as tourists. The tourist destination marketer can develop strategic marketing plans by identifying the influencing elements that contribute to the satisfaction of tourist satisfaction among University Malaysia Kelantan students. According to the data, tourist satisfaction among students at University Malaysia Kelantan is positively correlated with attractions, facilities, and destination image. Keywords: Tourist satisfaction, attraction, facilities, destination image.